HISTAMINE IN PET FOOD - Jakšić, Sandra; Galić, Tamara; Gardić, Ema; Kačarević, Tomislav; Nešić, Ksenija; Popov, Nenad; Živkov Baloš, Milica (Food and Feed Research, 2026)
Histamine is a biogenic amine formed by microbial decarboxylation of histidine and serves as a significant indicator of protein degradation in animal-based raw materials. Although traditionally associated with fish and fishery products, recent studies have confirmed its presence in pet foods containing fish and meat meals. Factors such as improper storage, elevated temperatures, and prolonged pre-processing intervals significantly contribute to the accumulation of histamine. Regulatory limits for histamine exist in foods intended for human consumption; however, comparable legal thresholds for pet food are currently lacking. Nevertheless, elevated histamine levels may negatively impact palatability, nutrient absorption, and animal health, particularly in sensitive populations such as juveniles and immunocompromised pets. This study examines histamine levels in various animal-derived raw materials and commercial pet foods (both dry and canned), with a particular focus on chicken, game, and fish meals. An HPLC-UV method was used to analyse 13 protein-rich raw materials for pet food samples and 14 pet food samples. Histamine was not detected in shrimp, lamb, quail or pork meals. In chicken and fish meals, histamine content ranged from 23.86±2.60 to 256.98±14.69 mg/kg. In 8 out of 10 dry pet food samples, histamine levels ranged from 9.18±0.56 to 54.24±4.12 mg/kg. Canned pet food samples were free of detectable histamine.